PENGARUH MODAL SOSIAL PETANI TERHADAP PENGEMBANGAN PANGAN LOKAL PADA PROGRAM DESA MANDIRI PANGAN DI KECAMATAN GEDANGSARI KABUPATEN GUNUNGKIDUL - , NURUL ANINDYAWATI; , Ir. Roso Witjaksono,MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to find out : (1) the level of social capital of farmers on local food development in food antonomous village program (2) the factors that influence social capital, (3) the influence of social capital on the development of local food. The research was conducted in Mertelu village,Gedangsari Sub-district, Gunungkidul regency.The samples of the research were farmers who join food antonomous village program . The basic method used in this research was descriptive analytic with survey technique. From Mertelu Village there were 6 samples of farmer groups taken by random sampling. Then 10 samples of farmer group was taken from each farmer group by using simple random sampling, so that there were 60 farmers as the sample in this research. Data were analyzed used the proportion test, multiple linear regression analysis, and analysis of simple linear regression. The research results showed that social capital classified in high level and achieve 78,34%. Factor that significantly affect to social capital was the role of leaders of the farmerâs group, as high as farmer group leader role, as strong as farmerâs social capital.The factors that did not significantly affect include was age, education, motivation, activity farmers in farmer groups, the role of agricultural extension, and land size. The influence of social capital on the development of local food is positively significant.